Soil Improving Cropping Systems for Sustainable and Profitable Farming in Europe - Wyseure, Guido; Cuevas González, Julián; Poesen, Jean (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
A major challenge for the future is combining both the profitability and sustainability of agriculture. The European H2020 project SoilCare aims to identify, test, and evaluate soil-improving cropping systems (SICS) which contribute to the implementation of agricultural solutions across Europe (See: https://soilcare-project.eu/en/ for the project website). The project includes 16 study sites distributed across Europe. Each study site implemented short-term experiments during the duration of the project, and most also ran long-term experiments comparing soil quality as a function of different treatments, such as soil amendments, tillage, cover crops, nutrients, and organic matter inputs. In addition, eight work-packages assess different aspects encompassing reviewing the soil-improving cropping systems, the participatory analysis of implementation and selection, methodology and analysis, upscaling at the European level, policy analysis and support, and dissemination and communication. In this way, SoilCare works on a providing a holistic approach to soil quality, spanning from biophysical to human interactions at different scales. In this Special Issue, we aim to compile scientific findings on soil-improving cropping systems (SICS) based on field experiments, including the study of policy, upscaling, and dissemination.